Kriteria Ruang Sekolah Khusus Penyandang Autisme - Hafilda, Hafilda; Martana, Salmon Priaji (Waca Cipta Ruang, 2021)
Autism is a condition of children with developmental disorders. This condition encourages the establishment of special schools to accommodate children with autism. This special school must have specific standards and criteria so that children with autism can learn at school as well as in turn have adequate therapeutic facilities. This paper aims to describe the criteria of those special schools for children with autism, in particular the design criteria that can be applied to the interior of a building. The research was conducted with a qualitative approach using a literature survey method with a review of government regulations and design standards for spaces of children at special schools recommended for persons with autism. It is hoped that with an understanding of these design criteria, spaces for persons with autism in special schools can be designed more effective and efficient.